Teacher Strategies in the Process of Drawing the Principle of Rhythm in Fine Arts Learning in Elementary Schools - Arina Shofia Zumala; Wasis Wijayanto (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2026)
Introduction/Main Objectives: This study aims to describe the strategies used by teachers in rhythm-based drawing lessons, their implementation process in the classroom, and the impact of these strategies on elementary school students' understanding of the concept of rhythm and creativity. Furthermore, this study is expected to provide theoretical contributions as a reference in developing fine arts learning, as well as practical benefits for teachers in designing more meaningful learning. Research Methods: The research method used was a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. Data analysis was conducted using the Miles and Huberman interactive analysis model, which includes the stages of data reduction, data presentation, and conclusion drawing. Finding/Results: The results show that teachers have implemented several basic strategies, such as the use of visual examples and demonstration activities, but their implementation has not been carried out systematically and exploratory. The learning process still emphasizes the final product, so that students' understanding of the concept of rhythm and creativity has not developed optimally. Conclusion: The conclusion of this study indicates the need to strengthen learning strategies, utilize more varied visual media, and implement assessments oriented towards the concept of rhythm to improve the quality of fine arts learning in elementary schools.